1986
DOI: 10.1111/j.1744-7348.1986.tb07644.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of cereal aphids in winter wheat by natural enemies: aphid‐specific predators, parasitoids and pathogenic fungi

Abstract: SUMMARY Winter wheat fields on two farms in West Sussex were sampled in 1980 and 1981 for cereal aphids and their natural enemies. The grain aphid, Sitobion avenae was present in all 19 fields examined, but in no case did the populations increase to densities liable to cause economic damage. The observations strongly suggest that aphid population growth was stopped by aphid‐specific predators, hymenopterous parasitoids and fungal pathogens. In two fields in 1980, S. avenae population densities approximately eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 13 publications
1
44
1
Order By: Relevance
“…Already in 1985 and 1986, Chambers et al (Chambers et al, 1985(Chambers et al, , 1986 reported the economic importance of hoverfly species as aphidophagous biological control agents. Other studies highlighted the role of volatile compounds -coming from aphid-damaged plants and from aphids themselves -as semiochemical cues in the foraging process of female Syrphidae (Almohamad et al, 2006;Harmel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Already in 1985 and 1986, Chambers et al (Chambers et al, 1985(Chambers et al, , 1986 reported the economic importance of hoverfly species as aphidophagous biological control agents. Other studies highlighted the role of volatile compounds -coming from aphid-damaged plants and from aphids themselves -as semiochemical cues in the foraging process of female Syrphidae (Almohamad et al, 2006;Harmel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Episyrphus balteatus DeGeer is the most commonly recorded syrphid species on agricultural lands (Chambers et al, 1986) and was already studied to investigate predator prey location (Bargen et al, 1998). In order to study the relation between volatile emission from aphids and prey location by E. balteatus larvae, three aphid species were selected according to the volatile pattern they released.…”
Section: Introductionmentioning
confidence: 99%
“…Anthicid and 109 Selectivity of Insecticides to Natural Enemies coccinellid predators as well as aphidiid parasitoids are recognized by their relative importance in different agroecosytems (Chambers et al, 1986;Elmali, 1997;Miranda et al, 1998) are often observed in high abundance in brassica crops.…”
Section: Discussionmentioning
confidence: 99%
“…Coccinellid and anthicid predators (Elmali, 1997;Miranda et al, 1998) and braconid parasitoids (Chambers et al, 1986) are recognized as important mortality factors of aphids. Cycloneda sanguinea (L.) (Coleoptera: Coccinellidae) and Acanthinus sp.…”
Section: Introductionmentioning
confidence: 99%